Interleukin-37b Suppressed ILC2s in Children with Allergic Rhinitis - Qingxiang Zeng; Yinhui Zeng; Haiqing Xiao; Jinyuan Li; Chao Yang; Renzhong Luo; Wenlong Liu; Yanhui Wen (Hindawi Limited, 2023)
Background. Interleukin-37b is a fundamental inhibitor of innate and acquired immunity. Type 2 innate lymphoid cells (ILC2s) can secret type 2 cytokines and regulate allergic rhinitis (AR). However, the role of IL-37b in ILC2s in children with AR was not clear. Methods. We recruited 15 AR children and controls. The serum IL-37b levels and its relation with the frequency and functional phenotype of ILC2s. The regulation of IL-37b on ILC2s proliferation and function was confirmed using flow cytometry and enzyme-linked immunosorbent assay (ELISA). The mRNA expression of IL-1R8, IL-18Rα, and ICOSL was examined using RCR. The change of IL-37b protein level in serum during subcutaneous allergen immunotherapy (SCIT) was determined by ELISA. Results. We have demonstrated that both of the frequencies of blood ILC2s, IL-5+ILC2s, and IL-13+ILC2s in AR children were elevated compared with controls. The serum protein level of IL-37b was downregulated in AR, and it was negatively related to the frequency of ILC2s, IL-5+ILC2s, and IL-13+ILC2s. IL-37b increased the mRNA levels of IL-1R8, IL-18Rα, and ICOSL expressed by ILC2s. IL-37b suppressed the proliferation of ILC2s and the secretion of IL-5 and IL-13 from ILC2s. Finally, we found that IL-37b was increased in AR children after 3 years' SLIT, especially in the good response group. Conclusion. Our findings highlight the role of IL-37b in the suppression of ILC2s and establish a new therapeutic target in AR.